Ferulic Acid Suppresses Amyloid β Production in the Human Lens Epithelial Cell Stimulated with Hydrogen Peroxide. (20th March 2017) - Nagai, Noriaki; Kotani, Sachiyo; Mano, Yu; Ueno, Akina; Ito, Yoshimasa; Kitaba, Toshio; Takata, Takumi; Fujii, Noriko
Abstract : It is well known that oxidative stresses induce the production of amyloid β (A β ) in the brain, lens, and retina, leading to age-related diseases. In the present study, we investigated the effects of ferulic acid on the A β levels in H2 O2 -stimulated human lens epithelial (HLE) SRA 01/04 cells. Three types of A β peptides (A β 1-40, A β 1-42, and A β 1-43 ) were measured by ELISA, and the levels of mRNA for the expressed proteins related to A β production (APP, BACE1, and PS proteins) and degradation (ADAM10, NEP, and ECE1 proteins) were determined by quantitative real-time RT-PCR. H2 O2 stimulation augmented gene expression of the proteins related to A β production, resulting in the production of three types of A β peptides. Treatment with 0.1 μ M ferulic acid attenuated the augmentations of gene expression and production of the proteins related to the secretion of three types of A β peptides in the H2 O2 -stimulated HLE cells. These results provided evidence of antioxidative functions of ferulic acid for lens epithelial cells.